Positioning strategy in private clinics in Manabí; clinical case Calderón - Bahía de Caráquez - Calderón Intriago, Mario Patricio (2022)
The research work was carried out in order to be able to determine the basic strategies that lead to positioning in private clinics in Manabí, the Calderón clinical case, which is located in the city of Bahía de Caráquez, despite the multiple changes that the city suffered from the earthquake that largely devastated several sectors of the city, the health sector, despite not having the necessary means, was never left unprotected, which has caused this medical center to gain prestige in the market in relation to other units that provide the same benefits for the inhabitants of the town, we cannot ignore this important economic sector, since its development in terms of health depends to a large extent on it. For this, a descriptive methodology was carried out, in which techniques and instruments such as observation and documentary review were used, through a SWOT analysis to determine the predominance of strengths over weaknesses and opportunities in the face of threats. As a result, the Calderón clinic is recognized for the good treatment and quality of service it provides to its users, as well as it is recommended that within the clinic's plans an improvement in control, care of its medical equipment, which allows it to continue offering an optimal quality service.